Relationship between restraint use, engagement in social activity, and decline in cognitive status among residents newly admitted to long‐term care facilities. Issue 2 (28th January 2016) - Freeman, Shannon; Spirgiene, Lina; Martin‐Khan, Melinda; Hirdes, John P
Abstract : Aim: Declining cognitive function can negatively affect residents' quality of life (QOL) in long‐term care facilities (LTCFs). The present study examined the role of physical restraint use, use of antipsychotic medications, and engagement in social activities to affect change in cognitive status and drive cognitive decline among residents newly admitted to a LTCF. Methods: Secondary data analysis used interRAI Minimum Data Set 2.0 data gathered at admission and first follow‐up assessment ( n  = 111, 052). The interRAI Minimum Data Set 2.0 collects comprehensive information as part of regular clinical care, and is mandated for all LTCF in Ontario, Canada. Bivariate and logistic regression analyses investigated the roles of physical restraint use, antipsychotic medication use and social engagement affecting cognition, and were stratified based on the presence/absence of diagnosis of dementia. Results: At follow up, 16.1% of residents ( n  = 16 414) showed decline in cognition. Residents with one or more physical restraints (chair, trunk and limb) were at increased risk for cognitive decline evidenced among residents with and without a diagnosis of dementia. Antipsychotic medication use did not emerge as a strong predictor of cognitive decline. Social engagement was protective against cognitive decline, and more pronounced for residents without a diagnosis of dementia. Conclusion: Physical restraint use should be avoided, or used as a last resort. LTCFs should prioritize resident engagement in social activities in either formal activities or ad hoc, as soon as possible on entry to the LTCFs. Prioritizing social networks and greater participation in activities might decrease the risk for cognitive decline, thereby improving or maintaining resident quality of life.Geriatr Gerontol Int 2017; 17: 246–255.